2019
DOI: 10.1002/ijc.32720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the seventh and eighth editions American Joint Committee Cancer classification system in oral cavity squamous cell cancers

Abstract: The aim of our study was to evaluate the predictive ability of the American Joint Committee Cancer (AJCC) eighth edition (AJCC8) staging system for oral cavity cancers and validate these changes rendering the hypothesis of improving prognostication. We conducted a retrospective study including all oral cavity squamous cell carcinoma patients visiting our tertiary center from 2012 to 2015, staged as per the AJCC seventh edition (AJCC7) and AJCC8 systems. Stage-specific diseasefree survival (DFS) and overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…More specifically, 20 patients (9.8%) would have been shifted from stage I-II "early disease" to stage III-IV "advanced disease", while only 3 (1.5%) would have been downstaged. All these modifications in T and N classification and staging are consistent with other published reports [17,18]. Such an important stage migration, and in particular the shift from early to advanced disease, convey relevant implications in treatment planning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…More specifically, 20 patients (9.8%) would have been shifted from stage I-II "early disease" to stage III-IV "advanced disease", while only 3 (1.5%) would have been downstaged. All these modifications in T and N classification and staging are consistent with other published reports [17,18]. Such an important stage migration, and in particular the shift from early to advanced disease, convey relevant implications in treatment planning.…”
Section: Discussionsupporting
confidence: 88%
“…Coherently, T4a tumors are associated with the poorest results when focusing on loco-regional control. These data are in accordance with literature, as several reports from all over the world demonstrated higher predictive accuracy of the 8th TNM edition [17][18][19][20][21][22][23][24].…”
Section: What Is Gained?supporting
confidence: 92%
“…The 5-year overall survival for the cohort was surprisingly 52.1%, and the disease-free survival was 48.6%. Multiple studies have shown the 5-year overall survival of oral squamous cell carcinomas to be ranging from 79.9% to 60% for the entire spectrum of TNM stages 17–21 . An in-house study showed an overall survival of 68.4% for resectable advanced (stages III and IV) cases 6 .…”
Section: Discussionmentioning
confidence: 99%
“…There were 121 males and 52 females aged 40-67 years old and (52.8 ± 13.3) years old on average. The tumor-node-metastasis (TNM) stage of the patients was determined according to the 8th edition of TNM staging system for lip and oral cavity tumors jointly published by the American Joint Committee on Cancer and Union for International Cancer Control (SINGHAVI et al, 2020), including 33 cases of stage I, 41 cases of stage II, 47 cases of stage III and 52 cases of stage IV. Moreover, oral cancer was classified into 3 grades based on the pathological differentiation degree (KUKREJA et al, 2020), i.e.…”
Section: Baseline Clinical Datamentioning
confidence: 99%